Aplikasi Augmented Reality Magic Book Pengenalan Binatang Untuk Siswa TK - Gede Wahya Dhiyatmika, I Dewa; Putra, I Ketut Gede Darma; Mandenni, Ni Made Ika Marini (Lontar Komputer : Jurnal Ilmiah Teknologi Informasi; Vol. 6, No.2 Agustus 2015, 2015)
Augmented Reality is a technology combining 2 or 3 dimensional virtual objects into a real 3 dimensional environment and projected real time. Children at 5 to 7 years old, are in their golden age where they are getting more sensitive to stimulus and easier on learning new things, that they are easier on receiving new and interesting things. So, it seems to be important for children at this age to learn about living creature around them, one of it is learning about animals. Media about animal introduction for kindergarten students, such as book with 2 dimensional animal form, seems like incapable yet to excite children on learning about animal species. This Augmented Reality Magic Book Animals Introduction Application for Kindergarten Students has been developed using Android base with marker that identified 3 dimensional animal objects, their voices, and the informations about the animals using Augmented Reality Technology. Augmented Reality technology makes animal introduction to children become easier and more interesting, this application shows 3 dimensional form of animals and their voices with more innovative interface using Smartphone.
Keywords: Binatang, Augmented Reality, Magic Book, Marker, Siswa TK